Analisis Akurasi Penerjemahan Bahasa Arab Lewat Fitur Auto Translate pada Aplikasi Twitter - Kisno Umbar; Aisyah Adilah; Rahma Raihana Romadona; Muhammad Rafli (IAI Muhammadiyah Sinjai, 2023)
This study aims to describe the errors and accuracy of translation on automatic translation machines on the Twitter application and to find out the automatic translation procedures carried out on the Twitter application. The method used by the authors in this study is a qualitative research with a descriptive approach. The data obtained in this study was carried out by observation or indirect observation of uploads contained in the Twitter application where there were irregularities in the translation. Researchers utilize sources that come from Twitter users who use Arabic in their